2019
DOI: 10.1093/ofid/ofz360.1327
|View full text |Cite
|
Sign up to set email alerts
|

1463. The Rates of UTI Outpatient and Inpatient Visits from 2001 to 2015 Among an Insured Population

Abstract: BackgroundHospitalizations attributable to urinary tract infections (UTI) have increased in recent years. One possible reason for the increase in admissions is a lack of effective oral agents, due to increasing rates of antimicrobial resistance, necessitating treatment with IV antibiotics. Our objective was to compare the rates of inpatient vs. outpatient treatment for UTIs.MethodsWe used the MarketScan database to identify UTI inpatient and outpatient visits from January 2001 through September 2015. Incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this study, out of 32,521,146 patients who developed UTI, only 297,470 (0.91%) were hospitalized. [ 17 ] For greater accuracy, among hospitalized patients with UTIs, it was estimated that 66.7% of infections in inpatients were caused by ESBL-producing bacteria, according to a study by Ranjan et al [ 18 ] Therefore, the target population was estimated to be 53,689 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, out of 32,521,146 patients who developed UTI, only 297,470 (0.91%) were hospitalized. [ 17 ] For greater accuracy, among hospitalized patients with UTIs, it was estimated that 66.7% of infections in inpatients were caused by ESBL-producing bacteria, according to a study by Ranjan et al [ 18 ] Therefore, the target population was estimated to be 53,689 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Since the beginning of 21 st century both OPD visits and IPD admissions for UTI have been rising and so is the use of antibiotics. [ 5 ] Thus to minimize indiscriminate use, it is important to analyze current patterns of antibiotic prescription in uncomplicated UTI cases and compare them with the existing guidelines. Recent studies have found out sensitivity rates among pathogens for different antibiotics in different regions of India,[ 6 7 ] but somehow the aspect of drug efficacy in actual clinical settings in terms of symptom relief for the patients is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%